Efektivitas Program Unit Layanan sosial Perjalanan (UPSK) untuk banyak orang Disabilitas - Putri, Rani Julia; Malau, Hasbullah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Provincial Government through West Sumatra Regional Regulation no. 2 of 2015 guarantees that persons with disabilities have the same rights as society in general. To achieve this, the West Sumatra Social Service created a Unit Pelayanan Sosial Keliling (UPSK) program which is regulated in the West Sumatra Social Service Strategic Plan 2016-2021. However, from year to year there has been a decline in service beneficiaries due to the absence of budget funds from the APBN. This research uses descriptive qualitative method with purposive sampling technique. The research was conducted at the West Sumatra Social Service Office, South Solok District Office and people with disabilities in South Solok. The results of the study indicate that the UPSK program in South Solok Regency has not been effective, seen from: 1) The success of the program; 2) Target success; 3) Program satisfaction; 4) Input output level; 5) Achievement of overall goals. So it is hoped that program organizers will consider the comparison of the duration of program implementation with the number of people with disabilities, taking into account the affordability of service locations. Then the thing that needs to be noted is the continuity of the program and the renewal of services in other fields such as the economy, entrepreneurship, and education.